2011
DOI: 10.1186/1478-7954-9-49
|View full text |Cite
|
Sign up to set email alerts
|

Validating physician-certified verbal autopsy and probabilistic modeling (InterVA) approaches to verbal autopsy interpretation using hospital causes of adult deaths

Abstract: BackgroundThe most common method for determining cause of death is certification by physicians based either on available medical records, or where such data are not available, through verbal autopsy (VA). The physician-certification approach is costly and inconvenient; however, recent work shows the potential of a computer-based probabilistic model (InterVA) to interpret verbal autopsy data in a more convenient, consistent, and rapid way. In this study we validate separately both physician-certified verbal aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
70
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 15 publications
11
70
2
Order By: Relevance
“…The epidemiological transition is evident in the clinic visit data, where there has been a partial shift away from infectious diseases and undernutrition, with sexually transmitted infections, reproductive health problems and injuries becoming relatively more prominent 13 . The findings confirm previous work by Bauni and colleagues, who have shown that injuries and pregnancy-related conditions are now major causes of death among young men and women, respectively, living within the KHDSS area 25 . Although injury and HIV were not among the main reasons for visiting the health facility, other studies of the same community have shown injury and HIV as the main cause of death for young men and women, respectively 25 .…”
Section: Reasons For Facility Visitsupporting
confidence: 81%
See 1 more Smart Citation
“…The epidemiological transition is evident in the clinic visit data, where there has been a partial shift away from infectious diseases and undernutrition, with sexually transmitted infections, reproductive health problems and injuries becoming relatively more prominent 13 . The findings confirm previous work by Bauni and colleagues, who have shown that injuries and pregnancy-related conditions are now major causes of death among young men and women, respectively, living within the KHDSS area 25 . Although injury and HIV were not among the main reasons for visiting the health facility, other studies of the same community have shown injury and HIV as the main cause of death for young men and women, respectively 25 .…”
Section: Reasons For Facility Visitsupporting
confidence: 81%
“…The findings confirm previous work by Bauni and colleagues, who have shown that injuries and pregnancy-related conditions are now major causes of death among young men and women, respectively, living within the KHDSS area 25 . Although injury and HIV were not among the main reasons for visiting the health facility, other studies of the same community have shown injury and HIV as the main cause of death for young men and women, respectively 25 . Furthermore, Etyang and colleagues have reported that injuries were the most common cause of admission to Kilifi County Hospital among men, while infectious and parasitic diseases, and pregnancy-related complications were the most common among women 26 .…”
Section: Reasons For Facility Visitsupporting
confidence: 81%
“…The approach has been used to determine CODs among people of all ages in a wide range of settings (2, 7, 9–16); however, in Kenya, although VAs have been widely used as a tool for documenting CODs (7, 1214, 1721) , no study has yet been published in which the WHO-compliant InterVA-4 has been applied across deaths of all ages. The InterVA-4 model uses posterior probabilities for CODs, given an a priori distribution of CODs in the population and conditional probabilities for circumstances leading to death.…”
mentioning
confidence: 99%
“…But the illness history is not taken into account in the inter-VA-4 software [31]. Previous research has shown ‘a moderate agreement’ between causes of death derived from the inter-VA software and diagnosed by physicians [44,45]. Furthermore, in this study, inconsistency between the two methods of cause of death interpretation may be limited by the use of broad groups of causes of death.…”
Section: Discussionmentioning
confidence: 93%